Природа, культура й символічний обмін у драмі «Лісова пісня» Лесі Українки - Тхорук, Рая; Tkhoruk, Raіa (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті розглянуто художній світ драми-феєрії «Лісова пісня» з погляду параметрів доповнення й конфліктності знаків, персонажів та сюжетів, розпо- ділених за групами, співвідносними з природним та цивілізаційним (культур- ним). В основу покладено опис соціальної організації первісних суспільств Ж. Бодріяра. Інтерпретовано картини, які фіксують втрату навиків взаємодії зі світом уявлюваного, та їх кореляцію із сюжетами родинно-любовної теми й теми митця як іншого. The author of article considers fictional world of drama-fairy Forest Song and analyzes parameters of adding, opposition, complementation and conflicts in draw configuration of markers, figures and plots divided into segments of natural world and civilization. Study is based on some thesis about of symbolic exchange in primitive societies by J. Baudrillard. The group of drama forest inhabitants (demons) is interpreted to be phenomena of creative cultural activity of peasants and of natural peasant world as writher has constituted, not a level of human bodieness. In their structure it’s fixed an element of concept. The author analyzed scenes to show how social control do act, and how changes in protagonists’ emotional and spirit essence are realized due motif of symbolic death and birth. Function and peculiarities of situations of segregation are constituted. Some scenes which show destruction of competence and skill to cooperate with imaginative world are interpreted by author; it’s considered their correlation with the theme of artist as Another and with family and love stories.
Nature, Cultura and Symbolic Exchange in Fictional World of Drama-Fairy “Forest Song” by Lesіa Ukrainka
Keywords: код природного; символічний обмін; уявлюване; образ-символ; тема митця; селянська культура; cod of nature; symbolic exchange; creative cultural activity; image as symbol; theme of artist; peasant culture